2020
DOI: 10.2196/14768
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Electronic Health Toolkit (Our Whole Lives for Chronic Pain) to Reduce Chronic Pain in Patients With Health Disparities: Open Clinical Trial

Abstract: Background Chronic pain affects millions of Americans. Our Whole Lives, an electronic health (eHealth) toolkit for Chronic Pain (Our Whole Lives for Chronic Pain [OWLCP]), is a mind-body chronic pain management platform that teaches self-management strategies to reduce pain impact and pain medication use. Objective The primary goal of this study was to evaluate the feasibility of OWLCP in reducing pain impact and pain-related outcomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…The study team (licensed dietician or nutritionist [BO], a culinary-trained family medicine physician [LJM], and a mindfulness-trained family physician [PG]) adapted the content from OWL (version 2) to create OWL-H. Most of the original content of OWL (version 2) created for patients with chronic pain was used ( Table 1 outlines the new content that was added to strategies to reduce HTN) [ 24 ]. The third version added evidence-based self-management strategies for reducing HTN and cardiac risk factors such as cooking videos and recipes using the Dietary Approaches to Stop Hypertension (DASH) [ 32 , 33 ] and Mediterranean diets.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study team (licensed dietician or nutritionist [BO], a culinary-trained family medicine physician [LJM], and a mindfulness-trained family physician [PG]) adapted the content from OWL (version 2) to create OWL-H. Most of the original content of OWL (version 2) created for patients with chronic pain was used ( Table 1 outlines the new content that was added to strategies to reduce HTN) [ 24 ]. The third version added evidence-based self-management strategies for reducing HTN and cardiac risk factors such as cooking videos and recipes using the Dietary Approaches to Stop Hypertension (DASH) [ 32 , 33 ] and Mediterranean diets.…”
Section: Methodsmentioning
confidence: 99%
“…The OWL curriculum introduces patients to the principles of mindfulness practices, nutrition, stress reduction, and movement [ 22 , 23 ]. In 2017, OWL (version 2) was tested to determine its effectiveness as a stand-alone intervention for patients with chronic pain; participants showed significant reduction in depression, pain interference, and average pain impact, accompanied by 13% reduction in opioid use ( P =.03) [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The PROMIS-29 has been widely used including in populations with obesity and chronic pain. (37)(38)(39)(40)(41)(42)(43) Participants answered four questions addressing pain interference (Cronbach's Alpha = .94): "In the past 7 days, how much did pain interfere with your day to day activities", "work around the house", "your ability to participate in social activities", "with your household chores". Responses were on a scale from one to ve, and de ned as: not at all (1), a little bit (2), somewhat (3), quite a bit (4), very much (5).…”
Section: Methodsmentioning
confidence: 99%
“…Digital mental health interventions can potentially address the issues of accessibility, rising health care costs, low availability of therapeutic care, and other barriers [ 35 , 36 ] associated with standard in-person treatments for chronic pain [ 37 ] and mental health [ 38 , 39 ]. Studies have reported that digitally delivered mental health interventions have a positive role to play in the self-management of depression and anxiety [ 40 , 41 ] and have been found effective in reducing the impact of chronic pain on the quality of life [ 42 ].…”
Section: Introductionmentioning
confidence: 99%